A new species of Expanathura (Crustacea: Isopoda: Anthuroidea) from Iriomote Island, Japan, with a note on male polymorphism - Shiraki, Shoki; Shimomura, Michitaka; Kakui, Keiichi (Zootaxa, 2021)
We describe Expanathura monile sp. nov. from Iriomote Island, Okinawa, Japan, northwestern Pacific. This species resembles E. collaris, E. macronesia, and E. haddae in having very broad uropodal rami, a broad telson, and a moderately shortened pleopod 1 endopod, but differs from these three species in the female having (1) the head with a dorsal V-shaped band of brown pigmentation, (2) the antennular flagellum with 3–4 articles, (3) antennal peduncular article 2 with an outer triangular projection, (4) the uropodal endopod longer than wide, (5) the uropodal exopod with an acute triangular projection, (6) an oval telson, and (7) the posterolateral setae on the telson similar in length. We present a revised key to known species in the genus Expanathura and briefly discuss the male polymorphism observed in E. monile.